High-purity hydrogen gas production by catalytic thermal decomposition using mechanochemical treatment - Kumproa,K. (Elsevier Limited, 2015)
© 2014 Hydrogen Energy Publications, LLC. The objectives of this work, were to produce high-purity hydrogen gas from rice husk by two-step process and to study the effect of nickel hydroxide/nickel acetate/sodium acetate and calcium hydroxide on the concentration of gaseous products. The samples were characterized by X-ray diffraction (XRD) and thermogravimetry-mass spectroscopy (TG/MS). The gaseous products were analyzed by gas chromatography (GC). The results indicated that hydrogen gas was produced from the milled samples by heating at 400-600 °C with the low concentrations of methane, carbon monoxide and carbon dioxide. The highest concentration of hydrogen gas from milled samples with the catalyst, was approximately 95-97 %mol. Furthermore, the milled samples with the carbon dioxide capture agent gave the carbon dioxide concentration, was below 2 %mol.